Synthesis of composites with nanoscale silicon and silicate oxides with lithium using three-dimensionally driven ball mill - Norihiro Shimoi; Hirotaka Aonuma; Masae Komatsu (Scientific Reports)
Abstract To achieve high-performance electrochemical anodes properties, active materials of anodes with improved cycle performance were composited using Cu alloys, silicon oxides and Li compounds within a composite by a simple mechanochemical milling process. The three-dimensionally driven ball mill used as a mechanochemical apparatus in this study can independently control two axes and can perform combined milling and frictional movements realized by adjusting the rotational speed of the vessel. The composite consisting of silicon, lithium oxide and copper oxide using these movements has Si nanoparticles, amorphous silicon monoxide, and Si–Cu alloy compounds, and a layer of silicon oxide on its surface. The prepared composite achieved higher retention capacity, higher coulomb efficiencies of approximately 90% and longer-cycle performance than Si particles, indicating a considerable optimisation of electrical and ionic conductivities in the composite. As a result, the method developed enabled the control of Li content to compensate for the lack of Li ions in the composite and optimised cycle performance with Cu alloys, oxides and Li compounds in the composite.